2021
DOI: 10.1097/cm9.0000000000001730
|View full text |Cite
|
Sign up to set email alerts
|

Independent and joint association of physical activity and sedentary behavior on all-cause mortality

Abstract: Backgrounds: Physical activity (PA) and sedentary behavior (SB) have been associated with mortality, while the joint association with mortality is rarely reported among Chinese population. We aimed to examine the independent and joint association of PA and SB with all-cause mortality in southern China. Methods: A cohort of 12,608 China Hypertension Survey participants aged ≥35 years were enrolled in 2013 to 2014, with a follow-up period of 5.4 years. Baseline self-repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 50 publications
(82 reference statements)
2
15
1
Order By: Relevance
“…Overall, our study demonstrates a positive association of self-reported sitting time with all-cause mortality and major CVD, which is in line with previous meta-analyses (including studies using self-reported measurements from HICs) and recent prospective cohorts from China . Moreover, we found that the risk of composite outcome associated with sitting time increased in a linear manner, which was similar to a prospective cohort among 5638 older women from the US, demonstrating a linear relationship between objectively measured sedentary time and CVD .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Overall, our study demonstrates a positive association of self-reported sitting time with all-cause mortality and major CVD, which is in line with previous meta-analyses (including studies using self-reported measurements from HICs) and recent prospective cohorts from China . Moreover, we found that the risk of composite outcome associated with sitting time increased in a linear manner, which was similar to a prospective cohort among 5638 older women from the US, demonstrating a linear relationship between objectively measured sedentary time and CVD .…”
Section: Discussionsupporting
confidence: 90%
“…Thus far, current evidence has been almost exclusively in high-income countries (HICs) and China . Previous studies suggested that the contextual patterns in which sedentary behavior occurs might vary substantially by socioeconomic status and social class .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the currently available data suggest that the elderly do not engage in physical activity [ 25 ] and this lifestyle choice can lead to health implications [ 26 ] and higher mortality rates [ 27 , 28 ]. In fact, physical activity can improve depressive symptoms and quality of life in institutionalized elderly persons [ 29 ], and it can be used to prevent falls in this age group [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with SB<6h per day with a high PA, SB≥6h with inadequate PA would increase the risk of all-cause mortality. The negative effect of SB on mortality risk cannot be fully offset by increasing PA. For people with high PA, the risk of death remains higher for SB≥6h than for SB<6h [20]. Replacing sedentary time with PA would reduce the risk of death from CVD.…”
Section: Risk Factorsmentioning
confidence: 99%